Moisture-proof anti-precipitation calcium-zinc composite stabilizer for SPC floor and preparation method thereof

Through a composite stable system of calcium-zinc complex barrier agent, microcapsule repair agent, modified adsorption hydrophobic agent and flexible interface regulator, the metal ion precipitation problem of SPC floor under moisture and heat alternation and mechanical stress is solved, and efficient interface stability and long-life performance are achieved.

CN120518345APending Publication Date: 2025-08-22ANHUI HUAWEN PLASTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510668314.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

Existing calcium and zinc stabilizers are difficult to maintain long-term anti-precipitation performance under high humidity environments and dynamic mechanical stresses, resulting in insufficient moisture resistance of SPC floors in moisture-heat alternation and mechanical stress coupling scenarios, lack of dynamic protection, microcrack-induced failure, and decreased interface peeling strength.

Method used

A composite stable system of calcium-zinc complex barrier agent, microcapsule repair agent, modified adsorption hydrophobic agent, flexible interface regulator and free radical stability regulator is adopted. By forming a high chelation constant complex network at the PVC-CaCO3 interface, the microcapsule repair agent releases the core material during heat or shear for crack repair, the modified adsorption hydrophobic agent electrostatically adsorbs metal ions, the flexible interface regulator improves interface compatibility, and the free radical stability regulator captures active free radicals, and builds a multiple stable system.

Benefits of technology

In the long-term wet-heat alternation and light environment, the metal ion precipitation rate is significantly reduced, the interface stability and intensity are maintained, and the problems of easy precipitation and intensity attenuation of traditional calcium and zinc stabilizers in high humidity scenarios are solved, and the service life of SPC floors is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a moisture-proof anti-precipitation calcium-zinc composite stabilizer for an SPC floor and a preparation method thereof. The moisture-proof anti-precipitation calcium-zinc composite stabilizer comprises 35-40% of a calcium-zinc complexing barrier agent; 15%-20% of a response type microcapsule repairing agent; 15%-20% of a modified adsorption hydrophobic agent; 15%-20% of a flexible interface regulator; 1%-2% of a free radical stability regulator; the calcium-zinc complexing barrier agent, the response type microcapsule repairing agent and the modified adsorption water repellent agent construct a high-chelation net in the SPC floor through the synergistic effect of barrier, repairing and adsorption, a repairing core material is released in a response mode in a crack area, metal ions are captured, migration and precipitation of Ca / Zn are inhibited, and the SPC floor is repaired. A compatible anti-oxidation multi-dynamic protection network is formed by the flexible interface regulator and the free radical stability regulator; therefore, the problems of metal ion precipitation, crack propagation and water vapor erosion are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite stabilizers, in particular to a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC floors and a preparation method thereof. Background Art

[0002] SPC (Stone Plastic Composite) flooring is primarily made from polyvinyl chloride (PVC), highly filled calcium carbonate (50-70% by weight), and functional additives through a high-temperature extrusion and calendering process. Its application scenarios (such as kitchens and bathrooms) place stringent demands on the material's moisture resistance and long-term stability. As a core component of the PVC thermal stabilization system, calcium-zinc composite stabilizers are required to inhibit PVC degradation and prevent metal ion precipitation during processing and use. However, existing calcium-zinc stabilizers exhibit the following technical drawbacks when exposed to high humidity and dynamic mechanical stress: Insufficient moisture resistance: Traditional auxiliary components (such as hydrotalcite) rely on interlayer hydroxyl groups to adsorb metal ions. However, in high humidity environments, the interlayers of hydrotalcite absorb moisture and expand, forming ion diffusion channels, which in turn accelerate the migration of calcium and zinc ions and cause white spots on the surface. Lack of dynamic protection: Although phosphite synergists can complex metal ions, they have poor hydrolytic stability and generate acidic products under long-term hot and humid conditions, which aggravates PVC degradation and ion precipitation; Microcrack-induced failure: The microcracks generated during extrusion, calendering and use of SPC flooring become the preferred path for ion migration, and the existing static adsorption mechanism cannot achieve crack self-repair and dynamic blocking, resulting in a decrease in interface peeling strength.

[0003] The above problems make it difficult for existing calcium-zinc stabilizers to meet the long-term anti-precipitation requirements of SPC floors under alternating humidity and heat and mechanical stress coupling scenarios, severely limiting their application. Summary of the Invention

[0004] (1) Technical problems solved In response to the shortcomings of the existing technology, the present invention provides a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring and a preparation method, which solves the problem that the existing calcium-zinc stabilizer is difficult to maintain long-term anti-precipitation performance under the coupling of moisture and heat and mechanical stress.

[0005] (2) Technical solution To achieve the above objectives, in a first aspect, the present application provides a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring, comprising the following components by mass percentage: Calcium zinc complex barrier agent 35%-40%; Microcapsule repair agent 15%-20% Modified adsorption hydrophobic agent 15%-20%; Flexible interface regulator 15%-20%; Free radical stabilizing regulator 1%-2%; The calcium-zinc complex barrier agent comprises: first dissolving a multidentate carboxylic acid organic ligand containing a citrate or succinate skeleton in a water-alcohol mixed solvent and adjusting the pH to a neutral to weakly alkaline state; then slowly adding a mixed metal salt solution of CaCl2 and ZnSO4 dropwise to carry out a complex reaction; and after the reaction, centrifuging, washing, and vacuum drying to obtain a white powder having a complex constant logK ≥ 5; The microcapsule repair agent refers to a microcapsule powder with an average particle size of 5-10μm and heat-shear triggered release function, which is obtained by high-speed emulsification-in-situ polymerization cross-linking encapsulation using an imidazole ionic liquid-difunctional epoxy resin composite system as the core material and polycaprolactone diacrylate-low-branched polyethyleneimine prepolymer as the shell material. The modified adsorption hydrophobic agent refers to: after the surface hydroxyl groups of magnesium aluminum layered double hydroxide are activated, a silanization reaction is carried out with a KH-570 coupling agent in an organic solvent, and then vacuum drying and crushing are performed to obtain hydrophobic nanosheets; Flexible interface regulator refers to: polyether or ester type plasticizer synergist, pre-mixed with polymer masterbatch by mechanical mixing; The free radical stabilizing regulator refers to: premixing styrene-benzophenone type photoresponse agent and hindered phenol type free radical stabilizer to form a light-heat synergistic antioxidant system.

[0006] The reaction mechanism is as follows: the calcium-zinc complex barrier agent forms an ion complex barrier at the PVC or CaCO3 interface to inhibit metal ion migration; the microcapsule repair agent releases the core material when heated or sheared, achieving pillaring-curing tandem repair in the crack area; the modified adsorbent hydrophobic agent electrostatically adsorbs Ca²⁺ / Zn²⁺ and constructs a humidity-responsive water vapor barrier; the flexible interface regulator improves the dispersion of each inorganic / organic phase; and the free radical stabilization regulator captures active free radicals and delays the oxidation chain reaction. Together, these five components form a multi-stabilization system of "barrier-repair-adsorption-compatibility-antioxidation". The calcium-zinc composite stabilizer is mechanically mixed or melt-coated and dispersed with a polyvinyl chloride matrix, an inorganic filler, and a lubricant in a conventional proportion, and then subjected to a high-temperature extrusion-calendering process to produce a moisture-resistant and precipitation-resistant SPC floor. The resulting floor maintains interface stability and significantly reduces the metal ion precipitation rate under a high humidity-heat alternating environment.

[0007] Preferably, the calcium-zinc complex barrier agent uses triethyl citrate or diethyl succinate as a ligand, and contains three or more carboxyl sites in the molecular structure, which can form a tridentate or tetradentate coordination complex with Ca²⁺ and Zn²⁺, and form a stable adsorption network through electrostatic adsorption, hydrogen bonding or polar pairing with the filler (such as CaCO3) or PVC matrix interface in the SPC floor, forming a barrier layer to hinder the diffusion of metal ions; effectively inhibiting the migration and precipitation process of free metal ions.

[0008] Preferably, the calcium zinc complex barrier agent is obtained by: Step S01: Prepare ligand solution: Add deionized water and ethanol mixed solvent (volume ratio 1:1) into a three-necked flask, add triethyl citrate or diethyl succinate (ligand concentration controlled at 0.1-0.2 mol / L) under stirring, and heat to 60°C to fully dissolve; Step S02: adjusting the pH and promoting the complexation reaction: slowly adding triethylamine dropwise to stabilize the pH of the system at 7.5-8.0, maintaining a neutral to weakly alkaline state, to obtain a ligand solution; Step S03: Pre-preparation of metal salt solution: Prepare 0.2 mol / L CaCl2 and ZnSO4 solutions respectively, mix them in a molar ratio of (Ca²⁺:Zn²⁺=1:1 or 2:1), stir evenly and set aside to obtain a metal ion mixed solution; Step S04: Complexation reaction: slowly add the metal ion mixed solution dropwise to the ligand solution at a controlled dropwise rate (1 mL / min), maintain the reaction temperature at 60-70°C, and continue stirring for 2 hours; after the reaction is complete, continue aging and stirring for 30 minutes; collect the precipitate by centrifugation, and wash twice with deionized water and ethanol; Step S05: Drying: vacuum drying at 50-60° C. for 12 hours to obtain a white or light yellow powdery calcium-zinc complex barrier agent; Step S06: Product characterization: Detect the product by infrared spectroscopy to see if it has a characteristic carboxylate absorption peak (1540-1600 cm⁻¹); and use titration or complexometric titration to determine its stable complex constant logK≥5 to ensure the performance of the calcium-zinc complex barrier agent.

[0009] Preferably, the preparation method of the microcapsule repair agent includes the following steps: Step S11: Core material pretreatment: an imidazole-type ionic liquid (e.g., 1-ethyl-3-methylimidazolium-bis(fluorosulfonyl)imide) and a difunctional epoxy resin (e.g., bisphenol A diglycidyl ether or aliphatic diepoxy) are mixed in a mass ratio of approximately 4:6, 1 wt% of tris(dimethylaminomethyl)phenol is added as a latent accelerator, and the mixture is stirred at 60°C until a homogeneous transparent system is formed. The mixture is then ultrasonically degassed at 40 kHz for 15 minutes to remove bubbles, thereby obtaining a homogeneous core material phase. Step S12: Shell material modification and prepolymer reaction: Polycaprolactone diacrylate and low-branching polyethyleneimine (PEI, molecular weight ≈600) were mixed at a mass ratio of 10:2 at 50°C, and 0.5 wt% isophorone diisocyanate was slowly added dropwise for end group capping. Subsequently, 2 wt% maleic anhydride grafted polyolefin and 0.5 wt% tris(dimethylaminomethyl)phenol were added to delay the embedding of the accelerator into the shell layer and introduce acrylate groups compatible with the calcium zinc complex barrier agent ligand to obtain a crosslinkable shell material prepolymer. Step S13: In-situ polymerization and encapsulation of the microcapsule repair agent: The core material obtained in step S11 was slowly added dropwise to an aqueous phase containing 2 wt% polyvinyl alcohol and 1 wt% tris(dimethylaminomethyl)phenol, and emulsified at 8000 rpm for 15 minutes to form an oil-in-water emulsion with an average particle size of approximately 5–10 µm. The shell material prepolymer obtained in step S12 was added and continued to be emulsified uniformly. The temperature was raised to 55°C and kept warm for 4 hours to complete the cross-linking and curing of the shell layer and in-situ encapsulation. The mixture was naturally cooled, centrifuged (3000 rpm, 10 minutes), washed three times with deionized water, and vacuum dried (40°C, 24 hours) to obtain a light yellow microcapsule repair agent powder. Description: The average particle size of the obtained microcapsule repair agent is about 6-8µm, and the core material loading rate is ≈60%. When the temperature exceeds 80℃ or is subjected to shear stress, the microcapsule repair agent releases the core material.

[0010] Preferably, the modified adsorbent hydrophobic agent has enhanced interfacial affinity after being modified by a KH-570 coupling agent, and the preparation method of the modified adsorbent hydrophobic agent comprises the following steps: The surface of the magnesium-aluminum layered double hydroxide nanomaterial is activated with hydroxyl groups to enhance its interfacial reactivity. Subsequently, a coupling agent KH-570 (methacryloyloxypropyltriethoxysilane) is added to an organic solvent (such as ethanol) to undergo a silanization reaction, allowing the KH-570 coupling agent to form a dense organic functional layer on the surface of the magnesium-aluminum layered double hydroxide, thereby enhancing its affinity and stability with the organic phase. Finally, the modified magnesium-aluminum layered double hydroxide nanosheets are prepared by vacuum drying and pulverization to reduce water retention tendency and possess the dual properties of electrostatic adsorption and interfacial sealing. The modified magnesium-aluminum layered double hydroxide nanosheets and the reversibly curled network containing polyphenol-metal dynamic bonds self-assemble into a three-dimensional humidity-responsive skeleton through silane covalent bonds and coordination. In a high-humidity environment, the three-dimensional humidity-responsive skeleton spontaneously unfolds and instantly closes the ion migration and water vapor permeation channels. When the environment returns to a low-humidity state, the three-dimensional humidity-responsive skeleton curls and resets itself, thereby achieving dual ion-water vapor shielding. The explanation shows that the modified magnesium-aluminum layered double hydroxide nanosheets adsorb free Zn²⁺ or Ca²⁺ ions through electrostatic exchange, and the surface hydrophobic treatment effectively reduces the risk of water vapor condensation and penetration, which helps to block the prerequisites for precipitation in the microenvironment. Therefore, the modified adsorbent hydrophobic agent not only effectively improves the dispersibility and stability of magnesium-aluminum layered double hydroxide and the polymer matrix, but also gives it excellent metal ion capture and water vapor shielding capabilities.

[0011] Preferably, the microcapsule repair agent and the modified adsorbent hydrophobic agent form a synergistic response mechanism, which is used to improve the anti-precipitation ability of the SPC floor in the presence of microcracks and in a wet-heat alternating environment; when the crack is triggered, the imidazole cations in the core material are first embedded in the magnesium-aluminum layered double hydroxide layer to undergo an in-situ support-volume expansion reaction, which increases the interlayer spacing of the modified magnesium-aluminum layered double hydroxide nanosheets and produces a tensioning effect. Subsequently, the diepoxy component is cross-linked and cured under the action of the latent accelerator encapsulated in the shell material to form a dense and tough repair layer; this pillaring-curing series process simultaneously realizes a triple synergistic structure of crack filling-ion capture-self-tensioning and locking in the same crack zone; The modified adsorbent hydrophobic agent includes modified magnesium-aluminum layered double hydroxide nanosheets, whose outer hydrophobic organosilicon network forms a water vapor barrier on the crack surface and adsorbs free Ca²⁺ and Zn²⁺ through interlayer electrostatic coordination, inhibiting metal ion migration; The coordinated response mechanism goes through: Initial response stage: When the interface temperature rises or microcracks appear, the microcapsule repair agent releases the core material under the dual triggering action of heat and shear. The imidazole-type ionic liquid completes the intercalation support of the modified magnesium-aluminum layered double hydroxide nanosheets. The diepoxy component then flows to fill the cracks and synergistically solidifies with the latent accelerator, preventing crack propagation and water vapor penetration. Secondary protection stage: The modified adsorbent hydrophobic agent repels condensed water in the crack area through its hydrophobic surface and electrostatically adsorbs the enriched Ca²⁺ and Zn²⁺ ions, further weakening the precipitation driving force; Synergistic stabilization stage: The support-filling-adsorption process operates synergistically under dynamic working conditions to form a triple dynamic stabilization system of "crack induction repair, ion capture and neutralization, and water vapor shielding and blocking", thereby improving the long-term moisture resistance and anti-precipitation performance of the SPC floor.

[0012] Preferably, the styrene-benzophenone photoresponsive agent undergoes n-π excitation under visible light conditions to form a triplet intermediate, inducing the migration of the free radical reaction path and preferentially removing unstable free radical intermediates, thereby effectively intervening in the aging process and improving the long-term stability of the interface; the photoresponsive component in the hindered phenol free radical stabilizer is a copolymer containing a styrene-benzophenone structural unit, and the copolymer is excited by n-π transition under visible light or medium and low energy ultraviolet light to form a triplet excited intermediate, which then selectively reacts with peroxides or alkoxy free radicals in the free radical reaction path, thereby inhibiting the continued progress of the chain aging reaction; The explanation is that styrene-benzophenone photoresponses and hindered phenolic free radical stabilizers work synergistically to form a stable free radical capture network, enhance antioxidant capacity, and delay the calcium and zinc precipitation process induced by photoaging and thermal oxidation, thereby improving the interface stability and long-term service life of SPC floors in humid and alternating light environments.

[0013] Preferably, the moisture-resistant and precipitation-resistant calcium-zinc composite stabilizer is compounded with calcium salt, zinc salt, and lubricant in proportion and dispersed by mechanical mixing or melt coating process to form an SPC floor; the moisture-resistant and precipitation-resistant calcium-zinc composite stabilizer is applied as follows: the calcium-zinc composite stabilizer is mixed with calcium salt, zinc salt, lubricant, and polyvinyl chloride in a ratio of 0.5:3:3:1:10, and the SPC floor is prepared by a high-temperature extrusion and calendering process; the calcium salt is calcium carbonate, the zinc salt is any one of zinc stearate and zinc carbonate; the lubricant is any one of PE wax and paraffin wax, which is used to improve processing fluidity and reduce frictional heat.

[0014] To achieve the above objectives, in a second aspect, the present application provides a method for preparing a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring, comprising the following steps: Step 1: Preparation of calcium-zinc complex barrier agent: Dissolve a multidentate carboxylic acid organic ligand containing multiple carboxyl functional groups in a mixed solvent, adjust the pH to neutral to weakly alkaline, and then react with a mixed metal salt solution of Ca²⁺ and Zn²⁺. After the reaction is completed, separate and dry to obtain a stable complex with a complex constant logK ≥ 5; Step 2: Preparation of microcapsule repair agent: Using an imidazole-type ionic liquid-difunctional epoxy resin composite system as the core material, a microcapsule repair agent is constructed by in-situ polymerization. The shell material is composed of modified polycaprolactone acrylate and polyethyleneimine, and contains a delayed-release curing accelerator to obtain a microcapsule repair agent powder with an average particle size of 5-10 μm. Step 3: Preparation of modified adsorption hydrophobic agent: Surface modification of magnesium aluminum layered double hydroxide using silane coupling agent to impart hydrophobicity and metal ion adsorption capacity to obtain a nano-adsorbent with interface sealing and electrostatic capture functions; Step 4: Mix the calcium-zinc complex barrier agent, microcapsule repair agent, modified adsorption hydrophobic agent, flexible interface regulator and free radical stabilization regulator in a preset ratio, and evenly disperse them by mechanical mixing or melt coating to obtain a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring; Step 5: Extruding the prepared moisture-resistant and anti-precipitation calcium-zinc composite stabilizer together with the PVC raw material to prepare the SPC floor.

[0015] (3) Beneficial effects The present invention provides a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring and a preparation method thereof, which has the following beneficial effects: In the solution provided by the present invention, a calcium-zinc composite stabilizer is synergistically introduced into a calcium-zinc complex barrier agent, a microcapsule repair agent, a modified adsorbent hydrophobic agent, a flexible interface regulator and a free radical stabilization regulator in a preset proportion, so that the calcium-zinc complex barrier agent constructs a high chelation constant complex network at the PVC-CaCO3 interface to inhibit Ca²⁺ / Zn²⁺ migration. The microcapsule repair agent releases an imidazolium ionic liquid-epoxy core material in the crack area when heated or sheared to form a pillared-cured series repair layer. The modified adsorbent hydrophobic agent relies on hydrophobic silanized magnesium aluminum layered double hydroxide nanosheets to simultaneously adsorb metal ions and block water vapor penetration. The flexible interface regulator improves the interfacial compatibility between the inorganic filler and the polyvinyl chloride matrix and relieves stress concentration through the dual functions of plasticization and lubrication. The free radical stabilization regulator captures active free radicals under light-heat dual excitation conditions to delay the oxidation chain reaction, thereby respectively solving key failure mechanisms such as metal ion precipitation, crack propagation, water vapor erosion, interface debonding and thermal oxidation aging.

[0016] The calcium-zinc composite stabilizer provided in the solution relies on the synergistic effects of barrier-repair-adsorption-compatibility-antioxidation. It can dynamically and adaptively block ion migration, instantly seal cracks and inhibit water vapor condensation under long-term moisture-heat alternation and light environment, significantly reducing the frosting and calcium-zinc precipitation rate on the surface of SPC flooring, maintaining dimensional stability and interfacial bonding integrity, and fundamentally solving the technical problems of traditional calcium-zinc stabilization systems that are prone to precipitation, strength attenuation and shortened lifespan in high-humidity scenarios. DETAILED DESCRIPTION

[0017] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0018] Preparation Example 1-3, for preparing calcium zinc complex barrier agent: Preparation Example 1: Using triethyl citrate as the ligand, Ca²⁺:Zn²⁺=1:1, reaction temperature 65°C, addition rate 1mL / min, reaction time 2h, logK=5.3.

[0019] Preparation Example 2: Using diethyl succinate as the ligand and other conditions being the same as those in Example 1, log K was measured to be 5.1.

[0020] Preparation Example 3: Triethyl citrate and diethyl succinate (molar ratio 1:1) were mixed as the ligand. Other conditions were the same as those in Example 1, and log K = 5.2.

[0021] Preparation Example 4-6, used to prepare microcapsule repair agent: Preparation Example 4: The ratio of core material is imidazole ionic liquid: difunctional epoxy resin = 4:6, and the ratio of shell material is polycaprolactone diacrylate: low-branched polyethyleneimine = 10:2. Emulsify for 15 minutes and cure the shell for 4 hours.

[0022] Preparation Example 5: core material 5:5, shell material 12:2, the rest is the same as Example 4.

[0023] Preparation Example 6: core material 3:7, shell material 8:2, the rest is the same as Example 4.

[0024] Preparation Example 7-16, used to prepare moisture-resistant and anti-precipitation calcium-zinc composite stabilizer: Preparation Example 7: Use the following formula (total of components 100 wt%): Calcium zinc complex barrier agent (Preparation Example 1) 40wt%; Microcapsule repair agent (Preparation Example 4) 20wt%; Modified adsorption hydrophobic agent 20wt%; Flexible interface regulator 18wt%; Free radical stabilizing regulator 2wt%; Among them, the modified adsorbent hydrophobic agent is obtained by activating the surface hydroxyl groups of magnesium aluminum layered double hydroxide (LDH) nanosheets, reacting them with the silane coupling agent KH-570 in an ethanol solvent, and then vacuum drying and crushing them to obtain the obtained agent. The flexible interface regulator is obtained by premixing a polyether or ester plasticizer synergist (such as phthalates or polyethylene glycol derivatives) with a polymer masterbatch by mechanical mixing to form a uniformly dispersed interface compatibility regulator. The free radical stabilizing regulator is obtained by premixing a styrene-benzophenone photoresponse agent and a hindered phenol free radical stabilizer (such as antioxidant 1076) in a mass ratio of 1:1–1:3 and forming the result by melt blending.

[0025] The above-mentioned moisture-resistant and anti-precipitation calcium-zinc composite stabilizer was mechanically mixed with polyvinyl chloride matrix, CaCO3, and lubricant according to conventional proportions, and melt-extruded and calendered into a 2 mm thick test piece, marked as sample 1; Preparation Example 8: The difference from Preparation Example 7 is that the microcapsule repair agent adopts Preparation Example 5, which is marked as Sample 2. The rest is the same, and the output is marked as Sample 2; Preparation Example 9: The difference from Preparation Example 7 is that the microcapsule repair agent adopts Preparation Example 6. The rest is the same, and the output is marked as Sample 3.

[0026] Preparation Example 10: The difference from Preparation Example 7 is that the calcium zinc complex barrier agent adopts Preparation Example 2, and the rest is the same. The output is marked as Sample 4.

[0027] Preparation Example 11: The difference from Preparation Example 7 is that the calcium zinc complex barrier agent adopts Preparation Example 3, and the rest is the same. The output is marked as Sample 5.

[0028] Preparation Example 12: The difference from Preparation Example 7 is that the calcium zinc complex barrier agent is 37wt%, the responsive microcapsule repair agent is 18wt%, the modified adsorption hydrophobic agent is 18wt%, the flexible interface regulator is 19wt%, and the free radical stabilization regulator is 2wt%. The rest is the same, and the output is marked as Sample 6.

[0029] Preparation Example 13: The difference from Preparation Example 7 is that the calcium zinc complex barrier agent (Preparation Example 1) is 35wt%; the microcapsule repair agent (Preparation Example 4) is 20wt%; the modified adsorption hydrophobic agent is 20wt%; the flexible interface regulator is 20wt%; and the free radical stabilization regulator is 5wt%. The rest is the same, and the output is marked as Sample 7.

[0030] Preparation Example 14: The difference from Preparation Example 13 is that the calcium zinc complex barrier agent (Preparation Example 2) is 35wt%; the microcapsule repair agent (Preparation Example 2) is 20wt%; the modified adsorption hydrophobic agent is 20wt%; the flexible interface regulator is 20wt%; and the free radical stabilization regulator is 5wt%; the rest is the same, and the output is marked as Sample 8.

[0031] Preparation Example 15: The difference from Preparation Example 13 is that the calcium zinc complex barrier agent (Preparation Example 2) is 40wt%; the microcapsule repair agent (Preparation Example 2) is 15wt%; the modified adsorption hydrophobic agent is 20wt%; the flexible interface regulator is 20wt%; and the free radical stabilization regulator is 5wt%; the rest is the same, and the output is marked as Sample 9.

[0032] Preparation Example 16: The difference from Preparation Example 13 is that the calcium zinc complex barrier agent (Preparation Example 3) is 40wt%; the microcapsule repair agent (Preparation Example 3) is 15wt%; the modified adsorption hydrophobic agent is 20wt%; the flexible interface regulator is 20wt%; and the free radical stabilization regulator is 5wt%; the rest is the same, and the output is marked as Sample 10.

[0033] Control group 1: no calcium zinc complex barrier agent was added, and the rest was the same as in Example 7; Control group 2: no microcapsule repair agent was added, and the rest was the same as Example 7; Control group 3: no modified adsorption hydrophobic agent was added, and the rest was the same as in Example 7; Control group 4: No calcium zinc complex barrier agent, microcapsule repair agent and modified adsorption hydrophobic agent were added, and the rest was the same as Example 7.

[0034] The samples were aged for 168 h at 85% humidity and 60°C, then removed, cooled naturally to room temperature, and the surface moisture was wiped off. The samples were then placed in 100 mL of deionized water and allowed to stand for 24 h (at 25°C and 500 rpm). The supernatant was filtered and quantified using ICP-OES (Ca²⁺ determination wavelength: 315.9 nm, Zn²⁺ determination wavelength: 213.9 nm) with an external standard method, with a detection limit of 0.05 mg / L. Samples 1-10 and controls 1-4 were tested using the method of aging at 85% humidity / 60°C for 168 h, followed by ICP-OES determination of Ca²⁺ and Zn²⁺ concentrations in the precipitate, yielding the results in Table 1. Table 1

[0035] Table analysis: The Ca²⁺ precipitation amount of all example samples 1-10 was controlled at 4.0–5.3 mg / L, the Zn²⁺ precipitation amount was 1.0–1.7 mg / L, and the stress loss rate was 4.0–6.0%, which were much lower than those of the control group (Ca²⁺7.8–12.5 mg / L, Zn²⁺3.7–8.3 mg / L, and stress loss rate 11.0–16.0%). This shows that the present invention takes a high chelating constant calcium-zinc complex barrier agent as the core, and combines a responsive microcapsule repair agent, a modified adsorption hydrophobic agent, a flexible interface regulator, and a free radical stabilization regulator to construct a "barrier-repair-adsorption-compatibility-antioxidation" multiple dynamic protection network, which can significantly inhibit the migration and precipitation of metal ions, seal microcracks, and maintain the mechanical properties of the material, thereby verifying the effectiveness of the core invention.

[0036] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. Moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring, characterized by: Calculated by mass percentage, it includes the following components: Calcium zinc complex barrier agent 35%–40%; Responsive microcapsule repair agent 15%–20%; Modified adsorbent hydrophobic agent 15%–20%; Flexible interface modifier 15%–20%; Free radical stabilization regulator 1%–2%; The calcium-zinc complex barrier agent, responsive microcapsule repair agent and modified adsorption hydrophobic agent synergistically act through barrier, repair and adsorption to construct a high chelating network in the SPC floor, responsively release the repair core material in the crack area and capture metal ions, inhibiting the migration and precipitation of Ca²⁺ / Zn²⁺, and together with the flexible interface regulator and free radical stabilization regulator, forming a multi-dynamic protection network compatible with antioxidants.

2. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The calcium-zinc complex barrier agent is formed by complexing a multi-dentate polycarboxylic acid ligand containing a citrate and / or succinate skeleton with Ca²⁺ and Zn²⁺. The ligand contains at least three carboxyl sites, and the complex constant logK of the complex is ≥5.

3. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The core material of the responsive microcapsule repair agent is a composite system of imidazole ionic liquid and difunctional epoxy resin, and the shell material is polycaprolactone diacrylate modified low-branching polyethyleneimine, which can release the repair core material under heat or shear triggering.

4. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The modified adsorption hydrophobic agent is a magnesium aluminum layered double hydroxide nanosheet modified by silanization with a KH-570 coupling agent, and has both electrostatic coordination adsorption and surface hydrophobic sealing functions.

5. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The flexible interface regulator is a polyether or ester plasticizer synergist, which is used to improve the compatibility of the inorganic / organic phase interface and relieve system stress.

6. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The free radical stabilization regulator comprises a styrene-benzophenone type photoresponse agent and a hindered phenol type free radical stabilizer, forming a light-heat synergistic antioxidant system.

7. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: 37wt% of calcium zinc complex barrier agent, 18wt% of responsive microcapsule repair agent, 18wt% of modified adsorption hydrophobic agent, 19wt% of flexible interface regulator, and 2wt% of free radical stabilization regulator.

8. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The modified adsorbent hydrophobic agent has enhanced interfacial affinity after being modified by a KH-570 coupling agent. The preparation method of the modified adsorbent hydrophobic agent comprises the following steps: The surface hydroxyl groups of magnesium-aluminum layered double hydroxide nanomaterials are activated to enhance their interfacial reactivity. Subsequently, KH-570 coupling agent is added to an organic solvent for a silanization reaction, so that the KH-570 coupling agent forms a dense organic functional layer on the surface of the magnesium-aluminum layered double hydroxide, thereby enhancing its affinity and stability with the organic phase. After vacuum drying and pulverization, modified magnesium-aluminum layered double hydroxide nanosheets with reduced water retention tendency and possessing the dual properties of electrostatic adsorption and interfacial sealing are obtained.

9. The moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring according to claim 1, characterized in that: The moisture-resistant and precipitation-resistant calcium-zinc composite stabilizer is compounded with calcium salt, zinc salt and lubricant in proportion and dispersed through mechanical mixing or melt coating process to form the SPC floor.

10. A method for preparing a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring, for obtaining the moisture-resistant and anti-precipitation calcium-zinc composite stabilizer according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of calcium-zinc complex barrier agent: Dissolve a multidentate carboxylic acid organic ligand containing multiple carboxyl functional groups in a mixed solvent, adjust the pH to neutral to weakly alkaline, and then react with a mixed metal salt solution of Ca²⁺ and Zn²⁺. After the reaction is completed, separate and dry to obtain a stable complex with a complex constant logK ≥ 5; Step 2: Preparation of microcapsule repair agent: Using an imidazole-type ionic liquid-difunctional epoxy resin composite system as the core material, a microcapsule repair agent is constructed by in-situ polymerization. The shell material is composed of modified polycaprolactone acrylate and polyethyleneimine, and contains a delayed-release curing accelerator to obtain a microcapsule repair agent powder with an average particle size of 5-10 μm. Step 3: Preparation of modified adsorption hydrophobic agent: Surface modification of magnesium aluminum layered double hydroxide using silane coupling agent to impart hydrophobicity and metal ion adsorption capacity to obtain a nano-adsorbent with interface sealing and electrostatic capture functions; Step 4: Mix the calcium-zinc complex barrier agent, microcapsule repair agent, modified adsorption hydrophobic agent, flexible interface regulator and free radical stabilization regulator in a preset ratio, and evenly disperse them by mechanical mixing or melt coating to obtain a moisture-resistant and anti-precipitation calcium-zinc composite stabilizer for SPC flooring; Step 5: The prepared moisture-resistant and anti-precipitation calcium-zinc composite stabilizer is compounded with calcium salt, zinc salt and lubricant in proportion to prepare the SPC floor.